ChemInform Abstract: Pyrrolidine Catalyzed Reactions of Cyclopentadiene with α, β‐Unsaturated Carbonyl Compounds: 1, 2‐ versus 1, 4‐Additions. Issue 33 (August 2015) - Coskun, Necdet; Cetin, Meliha; Gronert, Scott; Ma, Jingxiang; Erden, Ihsan
Abstract The pyrrolidine‐catalyzed reactions of benzalacetones (I) with cyclopentadiene leads to isolable intermediate Michael adducts (III) and (IV), which are converted into 1, 2‐dihydropentalenes (V) at longer reaction times.